Can Science Help Construct a New Global Ethic? The Development and Implications of Moral Transformation Theory - Loye, David (Zygon, 1999)
This paper reports the results of a ten-year search for consensus among scientific findings on the nature of the origin and development of moral sensitivity and morality. Significant agreement on six underlying factors was found. Based on these foundations, a new theory of moral transformation and a scientific “global ethic” relating to the global ethic of Hans Kung and the Parliament of the World's Religions is proposed. Fields surveyed include psychology, sociology, political science, economics, history, and gender and feminist studies in social science; physics and biology in natural science; and brain research, archaeology, and both old and new evolutionary studies and theory, including chaos, self-organizing, and other nonlinear theories, in systems science.